Reduction of Electromagnetic Reflections in 3D Airborne Transient Electromagnetic Modeling: Application of the CFS-PML in Source-Free Media - Yanju Ji; Xuejiao Zhao; Jiayue Gu; Dongsheng Li; Shanshan Guan (International Journal of Antennas and Propagation)
To solve the problem of electromagnetic reflections caused by the termination of finite-difference time-domain (FDTD) grids, we apply the complex frequency-shifted perfectly matched layer (CFS-PML) to airborne transient electromagnetic (ATEM) modeling in a source-free medium. To implement the CFS-PML, two important aspects are improved. First, our method adopts the source-free Maxwell’s equations as the governing equations and introduces the divergence condition, consequently, the discrete form of Maxwell’s third equation is derived with regard to the CFS-PML form. Second, because our method adopts an inhomogeneous time-step, a recursive formula composed of convolution items based on a nonuniform time-step is proposed. The proposed approach is verified via a calculation of the electromagnetic response using homogeneous half-space models with different conductivities. The results show that the CFS-PML can reduce a 60 dB relative errors in late times. Moreover, this approach is also applied to 3D anomalous models; the results indicate that the proposed method can reduce reflections and substantially improve the identification of anomalous bodies. Consequently, the CFS-PML has good implications for ATEM modeling in a source-free medium.